A prediction model for photopatternable thickness of photocurable polymer nanocomposites containing carbon-based high-aspect-ratio fillers. (8th February 2022) - Bae, Minwoo; Woo, Seungpyo; Lee, Jae Min; Lee, Woochul; Yoon, Sang-Hee
Abstract: The spatial patterning of photocurable polymer nanocomposites (PnCs) with electrical conductivity provides high flexibility in fabricating microscale conductors on surfaces of any geometry. A quantitative characterization of the photopatternability of photocurable PnCs is of great concern in their lithography process. It is, however, still regarded as challenging to theoretically predict the photopatternable thickness of photocurable PnCs. Here, we establish a theoretical model on the phtopatternable thickness of photocurable PnCs containing carbon-based high-aspect-ratio (HAR) fillers. Our model is derived by modifying the Beer-Lambert law to fully consider UV light absorption and reflection in the fillers, after describing HAR fillers as spherical ones with an out-of-plane orientation parameter. The accuracy of the proposed model is verified by comparing the predicted results with the experimental data on graphite nanoflake (GnF)-reinforced SU-8 PnCs, GnF/SU-8 PnCs. The effect of filler content and UV exposure energy on the photopatterning error of photocurable PnCs containing carbon-based HAR filler is also extensively addressed. Graphical abstract: Image 1